Anti-Inflammatory and Antibacterial Potential of Qicao Rukang Powder in Bovine Subclinical Mastitis. (27th August 2021) - Imam, Bereket H.; Oladejo, Ayodele O.; Wu, Xiaohu; Yang, Jie; Ma, Xiaoyu; Shen, Wenxiang; Wei, Jiang; Yan, Zuoting; Ding, Xuezhi
Abstract : Background . Subclinical mastitis is one of the most common reproductive diseases in dairy cows. Qicao Rukang powder is a Chinese herbal compound mixture developed to treat subclinical mastitis in dairy cows by clearing heat, tonifying qi, and improving blood and milk circulation. The study aimed to determine the anti-inflammatory and antimicrobial efficacy of Qicao Rukang powder in treating subclinical mastitis in dairy cows at the manufacturer's recommended dose. Methods . Forty (40) Holstein dairy cows with milk somatic cell count (SCC) ≥ 500, 000 cellml −1 were randomly assigned to treatment ( n  = 20) and control ( n  = 20) groups. Cows in the treatment group were administered with 150 grams of Qicao Rukang powder orally for five days, while the control group received no treatment. The authors analyzed the milk SCC, milk composition, bacteriological cure rate of the drug, blood serum levels of interleukins (IL-6, IL-1 β, and IL-8), tumor necrosis factor (TNF- α ), and interferon gamma (INF- γ ) quantified by using ELISA kits on day 0 and day 6. Results . SCC of the treated group reduced very significantly (P < 0.001 ) compared with the control group. Milk fat, protein, and total solids increased significantly (P < 0.05 ) after treatment, whereas lactose and milk urea nitrogen levels showed a nonsubstantial rise. The bacteriological cure percentage of Qicao Rukang powder therapy was 77.8% for Aeromonas spp. (14 of 18), 75% for Pseudomonas spp. (6 of 8), and 100% for Acinetobacter spp. and Enterococcus spp. giving 81.8% cured for all isolates (27 of 33). Only 26.7% (8 of 30) of untreated cows recovered spontaneously. Analysis of IL-1 β, IL-6, and INF- γ in the blood serum of the treated group revealed a significant decrease (P < 0.01 ) with nonsignificant rises in TNF- α and IL-8 levels. Conclusions . This research demonstrates that Qicao Rukang powder has potent antibacterial and anti-inflammatory actions, supporting its use as an alternative to conventional treatment for subclinical dairy cow mastitis. However, further investigations will be required to explain the role of the active ingredients and the mechanisms involved in the pharmacological activities of the Qicao Rukang powder.